Microbial and Physicochemical Assessment of Soil Contaminated with Cassava Waste Water in Makurdi Metropolis - Joel Odo (Hasanuddin University, 2022)
Environmental pollution is a burning topic of the day. Air, water and soil are being polluted alike. Soil being a